Studi Korelasi Penerapan Manajemen Pendidikan dengan Keaktifan Belajar Pendidikan Agama Islam di Madrasah Aliyah Al Muayyad Surakarta - Mardhiyah Agung Wahyuningsih (Program Pascasarjana UNU Surakarta, 2023)
This research has the purpose to conduct a study of the application of educational management to the liveliness of the teaching process in Islamic religious education. This research takes place at MA Al Muayyad Surakarta. The general view states that the success of the teaching process is affected by educational management and the general view supports this research. However, this view still needs to be proven through continuous research and includes various related aspects in it. This research uses field research or descriptive qualitative as its method and was conducted by the author for 6 weeks in December 2022. The author conducted ethnographic observations and field notes related to educational management implemented by school leaders, and learning and teaching activities carried out by teachers and students. Implementation of Education Management has a correlation with the Activeness of the Religious Education Learning Process at MA Al Muayyad Surakarta, the preparation and implementation of the curriculum, infrastructure, active intra, and extracurricular student activities on positive goals and can function as educational elements that support the Implementation of Education Management.